AAV8 vector induced gliosis following neuronal transgene expression - McLeod, Faye; McDermott, Elaine; Mak, Shermin; Walsh, Darren; Turnbull, Mark; LeBeau, Fiona E. N.; Jackson, Andrew; Trevelyan, Andrew J.; Clowry, Gavin J. (Frontiers in Neuroscience, 2024)
Introduction: Expression of light sensitive ion channels by selected neurons has been achieved by viral mediated transduction with gene constructs, but for this to have therapeutic uses, for instance in treating epilepsy, any adverse effects of viral infection on the cerebral cortex needs to be evaluated. Here, we assessed the impact of adeno-associated virus 8 (AAV8) carrying DNA code for a soma targeting light activated chloride channel/FusionRed (FR) construct under the CKIIa promoter.Methods: Viral constructs were harvested from transfected HEK293 cells in vitro and purified.To test functionality of the opsin, cultured rodent neurons were transfected and the light response of transfected neurons was assayed using whole-cell patch-clamp recordings. In vivo expression was confirmed by immunofluorescence for FR. Unilateral intracranial injections of the viral construct were made into the mouse neocortex and non-invasive fluorescence imaging of FR expression made over 1-4 weeks post-injection using an IVIS Spectrum system.Sections were also prepared from injected mouse cortex for immunofluorescence staining of FR, alongside glial and neuronal marker proteins.In vitro, cortical neurons were successfully transduced, showing appropriate physiological responses to light stimulation. Following injections in vivo, transduction was progressively established around a focal injection site over a 4-week period with spread of transduction proportional to the concentration of virus introduced. Elevated GFAP immunoreactivity, a marker for reactive astrocytes, was detected near injection sites associated with, and proportional to, local FR expression. Similarly, we observed reactive microglia around FR expressing cells. However, we found that the numbers of NeuN+ neurons were conserved close to the injection site, indicating that there was little or no neuronal loss.In control mice, injected with saline only, astrocytosis and microgliosis was limited to the immediate vicinity of the injection site. Injections of opsin negative viral constructs resulted in comparable levels of astrocytic reaction as seen with opsin positive constructs.Discussion: We conclude that introduction of an AAV8 vector transducing expression of a transgene under a neuron specific promotor evokes a mild inflammatory reaction in cortical tissue without causing extensive short-term neuronal loss. The expression of an opsin in addition to a fluorescent protein does not significantly increase neuroinflammation.